Multiracial college students and mentoring: an intersectional perspective - Bell, Megan Elizabeth, author; Kuk, Linda, advisor; Quijano, Louise, committee member; Herrera, Andrea, committee member; Sisneros, Kathy, committee member (Colorado State University. Libraries, 2016)
The purpose of this mixed-methods, sequential, explanatory study was to investigate differences in the mentor preferences of first-year college students in terms of their multiple identities, with a focus on the experiences of those who self-identified as multiracial. Using a framework of intersectionality, the importance of social identities (race, gender, sexual orientation, first-generation and socioeconomic status) to first-year students in their ideal mentor was explored. During the first phase, responses from first-year college students at four different universities were analyzed from an adapted version of the Ideal Mentor Scale (Rose, 1999). In the second phase, two follow-up focus groups were conducted with multiracial college students, which helped to further inform and explain the quantitative results. Of the three IMS subscales, quantitative results indicated that multiracial college students prefer a mentor who demonstrated characteristics related to the construct of Integrity. However, open-ended survey questions and focus-group data provided evidence for mentor preferences that were more aligned with the Relationship construct. Statistically significant differences were found only for the variables of sexual orientation and first-generation and socioeconomic status, with no significant interaction effects of any of the variables with multiracial identity. The quantitative and qualitative findings from the two phases of the study are discussed using an intersectional lens, with reference to prior research. Implications and recommendations are provided.